Encyclopaedia of medicinal plants (Vol.III) - Biswas Probir Kanti (Dominant publications,New Delhi, 2006)
Reference Books
ENGLISH
Keywords: Encyclopaedia of medicinal plants (Vol.III); Reference Books; Reference Books